Nanowatt analog circuit design for AIoT sensors - Lee, Hei Yip (Nanyang Technological University, 2024)
The tremendous development of Artificial Intelligence (AI) and Internet of Things (IoT) has been flourishing and propelled our society to an advanced platform. One of the practical applications that integrates AI into IoT technologies is Artificial Intelligence of Things (AIoT) sensor. It is an always-on sensor device installed at remote areas that monitors external surrounding factors. Consequently, it is expected to work with low power consumption to ensure its stable operation for any possible event detection. The comparator circuit block working in AIoT sensor plays a pivotal role of filtering any input signal to produce a reliable output. Therefore, the comparator only triggers the operation of AIoT sensor when there is true event detected. The design of a nanowatt comparator for AIoT sensors is presented in this final year project. The comparator core block is designed in Cadence Virtuoso EDA environment by employing advanced CMOS technology process node. It operates under subthreshold region to achieve energy efficiency. Additionally, it encompasses preamplifier, decision-making and output buffer stages to generate a reliable rail-to-rail output signal. The implementation of hysteresis window in comparator circuit blocks can effectively prevent erroneous switching states of comparator output due to external interferences. Moreover, the current reference circuit is employed to provide a constant DC biasing current source for stable operation of comparator core block across various conditions. Hence, the total power consumption of the circuit blocks is 10.308nW, when setting supply voltage as 1V.